Unified Power Quality Conditioners Based Different Structural Arrangements: A Comprehensive Review - Heenkenda A.; Elsanabary A.; Seyedmahmoudian M.; Mekhilef S.; Stojcevski A.; Aziz N.F.A. (Institute of Electrical and Electronics Engineers Inc., 2024)
Mitigating power quality issues in distribution systems is of utmost importance to both electricity consumers and suppliers as it improves the distribution system's efficiency, reduces electricity costs, maintains continuous supply, and diminishes the requirement for frequent maintenance. Custom power devices were introduced to eliminate power quality issues like voltage sags, swells, transients, imbalances, and current harmonics arising in distribution systems. Unified power quality conditioner (UPQC) is one such frequently used custom power device that enhances the power quality of distribution systems. Various structural arrangements of UPQCs with improved performance capability were introduced within the last few decades. The main aim of this paper is to review the most frequently explored UPQC models in literature and to observe the impact of these UPQC structural configurations on their performance as well as that of the overall distribution system. Also, this study investigates the properties, applications, and control techniques used by these structural configurations of UPQCs to mitigate power quality issues. 2013 IEEE.